2002
DOI: 10.1046/j.0014-2956.2002.02751.x
|View full text |Cite
|
Sign up to set email alerts
|

SMAP‐29 has two LPS‐binding sites and a central hinge

Abstract: The CD spectra of SMAP-29, an antimicrobial peptide from sheep, showed disordered structure in aqueous buffers, and significant helicity in membrane-like environments, including SDS micelles, lipopolysaccharide (LPS) dispersions, and trifluoroethanol buffer systems. A structure determined by NMR in 40% perdeuterated trifluoroethanol indicated that residues 8-17 were helical, residues 18-19 formed a hinge, and residues 20-28 formed an ordered, hydrophobic segment. SMAP-29 was flexible in 40% trifluoroethanol, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
114
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 36 publications
(242 reference statements)
9
114
0
Order By: Relevance
“…As discussed below, it has been widely noted in literature that many 7 structural characteristics are similar for AMPs and anti-endotoxic peptides, e.g., positive charge and amphiphilicity, and many anti-endotoxic peptides are indeed also AMPs. This was illustrated, e.g., by Tack et al who investigated variants of the antimicrobial peptide SMAP-29, and found a good correlation between minimal affective concentrations (MECs) for bacteria killing, on one hand, and LPS binding affinity, on the other (Figure 3) (15). Although many anti-endotoxic peptides are also AMPs, the reverse does not necessarily hold, suggesting that the membrane binding characteristics of AMPs, or underlying characteristics resulting in membrane binding and rupture, constitute a necessary, but not sufficient, requirement for anti-endotoxic effects.…”
Section: Effects Of Peptide Physicochemical Properties On Lps Bindingmentioning
confidence: 93%
“…As discussed below, it has been widely noted in literature that many 7 structural characteristics are similar for AMPs and anti-endotoxic peptides, e.g., positive charge and amphiphilicity, and many anti-endotoxic peptides are indeed also AMPs. This was illustrated, e.g., by Tack et al who investigated variants of the antimicrobial peptide SMAP-29, and found a good correlation between minimal affective concentrations (MECs) for bacteria killing, on one hand, and LPS binding affinity, on the other (Figure 3) (15). Although many anti-endotoxic peptides are also AMPs, the reverse does not necessarily hold, suggesting that the membrane binding characteristics of AMPs, or underlying characteristics resulting in membrane binding and rupture, constitute a necessary, but not sufficient, requirement for anti-endotoxic effects.…”
Section: Effects Of Peptide Physicochemical Properties On Lps Bindingmentioning
confidence: 93%
“…In addition to the direct antimicrobial effects, mammalian CAMPs possess other modulatory activities, such as LPS-neutralizing (20,21) and IL-8-stimulating activities (22,23,28,38,39). Furthermore, the LPS-binding activities are often positively correlated with their antibacterial activities (21).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of peptides to LPS was expressed as a percentage of absorbance developed by 0.1 mg peptide. Additionally, the LPS-binding isotherms of trout CAMPs and their truncated variants were quantified by the kinetic chromogenic Limulus amebocyte lysate assay (QCL-1000 kit; Lonza) as previously described (21,37).…”
Section: Lps-binding Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of DCD includes a highly flexible N-terminal helical region and a relatively ordered C-terminal helical region. A structural homology search based on the helix-hingehelix motif suggests DCD resembles a variety of antimicrobial peptides, including cecropin A, gaegurin 4 (GGN4) and SMAP-29 (23,26,27). DCD-1L shows particular similarity to SMAP-29, an antimicrobial peptide from sheep (27) that presents a flexible N-terminal region (residues 1 to 6), a helical region (residues 8 to 17), a C-terminal helical region (residues 20 to 28) and a hinge segment (Gly18 and Pro19).…”
mentioning
confidence: 99%